2020
DOI: 10.3390/ijerph17041426
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Molecular Aspects of Malignant Fibrous Histiocytoma Patients: A Systematic Review of the Literature

Abstract: Malignant fibrous histiocytoma is one of the most common soft tissue sarcomas in adults. It occurs only occasionally in oral soft tissues, and knowledge about its characteristics is based on a limited number of cases reported in the literature. Malignant fibrous histiocytoma belongs to the group of soft tissue sarcomas and makes up less than 10% of soft tissue sarcomas. For therapeutic purposes, complete exeresis of the lesion (macroscopic and microscopic) is performed because they have frequent recurrences. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 65 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…6 In 2012, WHO elucidated that diagnosis of UPS could be made only if "no definable line of differentiation" could be established. 4,6 However, the previous term MFH is still widely used by clinicians and pathologists. 4 UPS is more frequent in patients aged between 50 and 70 years with prevalence for males, who account about 65% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 In 2012, WHO elucidated that diagnosis of UPS could be made only if "no definable line of differentiation" could be established. 4,6 However, the previous term MFH is still widely used by clinicians and pathologists. 4 UPS is more frequent in patients aged between 50 and 70 years with prevalence for males, who account about 65% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 However, the previous term MFH is still widely used by clinicians and pathologists. 4 UPS is more frequent in patients aged between 50 and 70 years with prevalence for males, who account about 65% of cases. 12 As reported in literature, the usual clinical presentation is a fast-growing exophytic mass, painless, with or without ulceration and able to expand over a few weeks or months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicate future strategies for preventive measures for hypertensive children and adolescents. Zhurakivska K [ 12 ] focused on malignant fibrous histiocytoma as one of the most common soft tissue sarcomas in adults and found that further studies are necessary in order to standardize the approach to patients affected by oral malignant fibrous histiocytoma.…”
mentioning
confidence: 99%